Heart ablation using a planar rectangular high intensity focused ultrasound transducer and MRI guidance - Lafon, Cyril; Birer, Alain; Mylonas, Nicos; Damianou, Christakis A.; Iosif, Demitris; Chapelon, Jean Yves; Kyriakou, Panagiotis; Couppis, Andreas; Ioannides, Kleanthis; Chavrier, Francoise (My University, 2011)
The aim of this study was to evaluate the performance of a flat rectangular (3×10 mm2) MRI compatible transducer operating at 5 MHz in creating deep lesions in heart at a depth of at least 15 mm. The size of thermal necrosis in heart tissue was estimated as a function of power and time using a simulation model. The system was then tested in freshly excised heart of pig and lamb. In this study we were able to create lesions 15 mm deep with an acoustic power of 6W for an exposure of approximately one minute. The contrast to noise ratio (CNR) between lesion and heart tissue was evaluated using Fast Spin Echo (FSE). With T1W FSE the CNR value was approximately 22. Maximum CNR was achieved with repetition times (TR) between 300 and 800 ms. With T2W FSE the corresponding CNR was approximately 13. The transducer was tested in rabbits in vivo and despite the motion of the heart; it was possible to create thermal lesions. © 2011 American Institute of Physics.
Keywords: Heart ablation; HIFU transducer MRI guidance